Cost‐Effectiveness of a Statewide Campaign to Promote Aspirin Use for Primary Prevention of Cardiovascular Disease. Issue 12 (23rd December 2015) - Michaud, Tzeyu L.; Abraham, Jean; Jalal, Hawre; Luepker, Russell V.; Duval, Sue; Hirsch, Alan T.
Abstract : Background: The U.S. Preventive Services Task Force in 2009 recommended increased aspirin use for primary prevention of cardiovascular disease (CVD) in men ages 45 to 79 years and women ages 55 to 79 years for whom benefit outweighs risk. This study estimated the clinical efficacy and cost‐effectiveness of a statewide public and health professional awareness campaign to increase regular aspirin use among the target population in Minnesota to reduce first CVD events. Methods and Results: A state‐transition Markov model was developed, adopting a payer perspective and lifetime time horizon. The main outcomes of interest were quality‐adjusted life years, costs, and the number of CVD events averted among those without a prior CVD history. The model was based on real‐world data about campaign effectiveness from representative state‐specific aspirin use and event rates, and estimates from the scholarly literature. Implementation of a campaign was predicted to avert 9874 primary myocardial infarctions in men and 1223 primary ischemic strokes in women in the target population. Increased aspirin use was associated with as many as 7222 more major gastrointestinal bleeding episodes. The cost‐effectiveness analysis indicated cost‐saving results for both the male and female target populations. Conclusions: Using current U.S. Preventive Services Task Force recommendations, a state public and health professional awareness campaign would likely provide clinical benefit and be economically attractive. With clinician adjudication of individual benefit and risk, mechanisms can be made available that would facilitate achievement of aspirin's beneficial impact on lowering risk of primary CVD events, with minimization of adverse outcomes.